Global, regional and national burden of stroke and subtypes burden in women of reproductive age: insights based on Global Burden of Disease 2021 - Huan Lu; Wenhao Zhang (BMC Public Health)
Abstract Background The global burden of stroke among women of reproductive age is of significant concern. We aimed to leverage the Global Burden of Disease 2021 (GBD 2021) to estimate the prevalence, Years Lived with Disability (YLDs), and Disability-Adjusted Life Years (DALYs) rates for pathological types of strokes in women of reproductive age, as well as to examine their association with the sociodemographic index (SDI). Methods We utilized stroke data for women of reproductive age from 204 countries and territories from 1990 to 2021. The Annual Percentage Change (APC) was calculated, and the Average Annual Percentage Change (AAPC) was estimated to analyze trends in the burden of stroke. APC was used to measure the change in indicators over specific time intervals, assisting in describing the annual average rate of change in disease trends or other health metrics, and thereby providing insights into the direction and magnitude of disease burden changes. AAPC, typically derived as the weighted average of APC over a period, was used to assess long-term trends in time-series data, reflecting the overall trend while mitigating the influence of short-term fluctuations. This approach provides a solid basis for disease burden research and public health policy making. Additionally, the study explored the impact of risk factors for different pathological types on DALYs rates across various age groups and the 27 GBD super-regions. Statistical significance was set at P < 0.05. The analyses were conducted using the Joinpoint Trend Analysis Software and R 4.4.2. Results The overall burden of stroke in women of reproductive age worldwide shows a downward trend, with the prevalence rate of AAPC at -0.22, YLDs rate of AAPC at -0.33, and DALYs rate of AAPC at -1.27. However, the prevalence of ischemic stroke showed an upward trend, with an AAPC of 0.08. In 2021, the Nauru region bore the highest burden of stroke in women of reproductive age, with prevalence, YLDs, and DALYs rates reaching 1,223.56 (95% UI: 1,180.50 to 1,271.92), 241.44 (95% UI: 173.40 to 311.30), and 2,646.68 (95% UI: 1,977.34 to 3,663.05), respectively. Our analysis revealed that the indicators for ischemic stroke and intracerebral hemorrhage (ICH) generally declined over time and with increasing SDI values, whereas the burden of subarachnoid hemorrhage (SAH) initially increased before decreasing. When analyzing different age groups, we found that the burden of stroke in women of reproductive age increases with age. Between 1990 and 2021, the stroke burden decreased across all age groups within the reproductive years. The 15–19 age group exhibited the most significant decrease in prevalence rate, with an AAPC of -0.59; the 20–24 age group showed the most notable decline in YLDs rate, with an AAPC of -0.87; and the 35–39 age group experienced the largest reduction in DALYs rate, with an AAPC of -1.82. We identified 23 risk factors associated with stroke-related DALYs in reproductive-aged women. Compared with 1990, the strength of the associations between metabolic risk factors and stroke-related disability-adjusted life years was greater in 2021, with "High systolic blood pressure" and "High LDL cholesterol" demonstrating the most pronounced links. Moreover, trend analyses from 1990 to 2021 indicated that the associations of "Diet high in sugar-sweetened beverages" (AAPC = 2.33), "High body-mass index" (AAPC = 1.81), "High temperature" (AAPC = 0.77), and "High fasting plasma glucose" (AAPC = 0.51) with stroke-related DALY rates increased significantly over time. "Ambient particulate matter pollution" did not exhibit a statistically significant association, and the remaining seventeen risk factors showed declining trends in their associations. Conclusions While the global burden of stroke in women of reproductive age has decreased, significant burdens remain in certain regions and age groups compounded by multiple risk factors. Understanding these trends will help to guide future policy recommendations aimed at alleviating the associated burden.